THE EFFECT OF PROBLEM BASED LEARNING MODEL ON STUDENTS MATHEMATICAL CRITICAL THINKING ABILITY - Mufidah, Hasna; Caswita, Caswita; Wijaya, Agung Putra (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
This quasi-experimental study sought to assess the impact of the problem-based learning model on students' abilities in mathematical critical thinking. The population for this study consisted of all seventh-grade students at SMP Negeri 8 Bandar Lampung during the 2024/2025 academic year, totaling 231 students distributed across eight classes. The samples in this study were selected from two groups of 28 students and 27 students, chosen through cluster random sampling. The research design employed was a pretest-posttest group design. The data for this study were quantitative, collected from tests assessing students' mathematical critical thinking abilities. According to the results of hypothesis testing using the t-test, students who engaged in the problem-based learning model demonstrated a more substantial increase in their mathematical critical thinking skills than those who participated in the STAD-type cooperative learning model. This finding suggests that the problem-based learning approach significantly influences the development of students' mathematical critical thinking abilities.